Analysis of Factors that Influenced the Participation Rates in Upper-secondary Vocational Schools in China - Huang, Junjun; Ye, Zhang (Journal of Technical Education and Training, 2021)
Vocational education and training has been treated as a good pathway to smoothly promote youth from school to the workplace. However, for many reasons, the vocational education in Asian countries is not as popular as general education, and the participation rate in vocational schools is normally lower than it is in general schools. This paper builds a theoretical model about the factors that influence the participation rate in Chinese upper-secondary vocational schools and explains the possible related indicators through a regression analysis method. The results show that the most positive factor is related to the number of male students in vocational schools, followed by the number of female vocational teachers. Other staff in vocational schools also have a positive effect, while the youth unemployment rate and the number of men vocational teachers both have negative relationships with the participation rate. In China, it is possible to improve the rates of new entrants into vocational schools from the aspects of the gender issues, the training methods for vocational teachers, and the social recognition of vocational education.